Ritual Adat sebagai Instrumen Konservasi Lingkungan: Studi TEK Suku Tengger - Mistianah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
This study analyzes the Yadnya Kasada and Labuhan rituals of the Tengger Tribe as conservation strategies for Bromo Tengger Semeru National Park through Traditional Ecological Knowledge (TEK). Employing a sequential explanatory mixed methods design with 50 informants and 5 ethnographic observations, the research reveals that sacred zoning during rituals effectively reduces anthropogenic activities, supports endemic vegetation regeneration, and maintains higher biodiversity in ritual zones compared to tourist areas. TEK transmission is facilitated by long-term residency and communal ritual communication but hindered by formal education modernization and mass tourism, with significant ecological impacts through soil fertility enhancement from organic offerings. The formulated adat-scientific partnership model based on GIS-TEK supports sustainable management through hybrid zoning, NDVI monitoring, and environmental education integration into the Merdeka Curriculum. Findings confirm TEK as adaptive volcanic "soft law" ecology, recommended for TNBTS Zoning Plan 2025-2030.